Dying to win : doping in sport and the development of anti-doping policy / Barrie Houlihan. - Houlihan, Barrie (Council of Europe, 2002)
This up-to-date overview of drug taking in sport is illustrated with specific cases in various pan-European and world sports events, and reflects the extent to which athletes will jeopardise their health to attain glory.